40 Years of Experience with the National Market System (NMS) Who Are the Winners and What Have We Learned? - Schwartz, Robert A.; Byrne, John Aidan; Stempel, Eileen (Zicklin School of Business Financial Markets Series, 2022)
XIII, 163 p.